REMOTE LABORATORY IN MOBILE DEVICES - LUSTIG, Frantisek (Trends in education, 2014)
Remote laboratories are new objects in the teaching of natural sciences. The paper presents new examples of remote experiments with special modular software ISES WEB Control based on JavaScript. These new remote experiments can be run both on standard PCs and notebooks, or in mobile devices - mobile phones, or tablets.
Keywords: Java apples; JavaScript; software ISES WEB Control JavaScript; mobile phone; tablet.